Topical Menthol for Treatment of Chemotherapy-induced Peripheral Neuropathy - Cortellini, Alessio (Indian J Palliat Care, 2017)
Chemotherapy-induced peripheral neuropathy is a frequent treatment-limiting factor that significantly impairs patients’ everyday life, also because of a lack of valid palliative options. Here, we report a case of a male patient with a history of metastatic colon cancer and previous chemotherapies. He came to our attention with a peripheral neuropathy that impaired his quality of life and could limit the further line of chemotherapy. We treated the neuropathy with menthol aqueous cream with benefit.